Coadaptación entre los ácaros (Arachnida: Klinckowstroemiidae) y coleópteros Passalidae (Insecta: Coleoptera) - Villegas-Guzmán, Gabriel A.; Francke, Oscar F.; Pérez, Tila M.; Reyes-Castillo, Pedro (Revista de Biología Tropical, 2012)
Co-adaptation between mites (Arachnida: Klinckowstroemiidae) and Passalidae beetles (Insecta: Coleoptera). Mites of the family Klinckowstroemiidae establish an association with beetles of the family Passalidae known as phoresy. In order to obtain information about this association, we analyzed the relationship between mites of the family Klinckowstroemiidae and beetles of the family Passalidae, as adult mites have been exclusively collected from host beetles. We examined 1 150 beetles collected in seven states of the Mexican Republic, and found 19 species of klinckowstroemiid mites associated with 168 passalids, that belong to 28 different species in 15 genera. Host specificity between species of both groups does not exist, as one spe- cies of passalid beetle can have several different symbionts; conversely, a given mite species can associate with passalid beetles of different species and even of different genera. This way, Odontotaenius zodiacus has been found associated with mites of seven species of the genus Klinckowstroemia. Besides, Klinckowstroemia valdezi is associated with five species of passalids. Furthermore, two and even three different species of mites have been found on one host beetle (synhospitality). The lack of congruence between the phylogenies of the mites and that of the beetles indicates that a process of co-adaptation by colonization is going on, because the association is due to the resources that passalid beetles can offer to the mites, like transportation, food and refuge. Since these resources are not host-specific, the klinckowstroemiid mites can climb onto virtually any species of passalid beetles occurring on the same habitat.